Improvement for UAV Urban SAR Tomography Based on Cylindrical Wave Model With Elevation Constraints - Rui Guo; Zishuai Ren; Yuxin Gao; Lianhuan Wei; Yuxiao Qin; Gang Xu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Synthetic aperture radar (SAR) tomography (TomoSAR) technology can solve the layover problem in SAR images and achieve three-dimensional (3D) imaging. Unmanned aerial vehicle (UAV) TomoSAR has developed rapidly in the field of urban surveying and mapping in recent years due to its advantages of flexible deployment, low cost, and ease of large-scale application. However, the low flight altitude of UAVs and the need to reduce the number of observations pose challenges to the classical TomoSAR imaging model based on plane wave geometry. To improve the 3D imaging quality of UAV TomoSAR in urban areas, this article proposes a 3D imaging method based on a cylindrical wave geometry model with refined elevation constraints. This method reconstructs the 3D imaging model to conform to the near-field principle. Meanwhile, the constraint range of the elevation solution space is determined through the proposed layover area labeling under the cylindrical wave model. The experiments with simulation and real data show that the proposed method can accurately recover building structures and exhibits commendable performance in deformation correction and ambiguity suppression.